2020
DOI: 10.3389/fonc.2020.01410
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Radiomics Nomogram Using Magnetic Resonance Images for Prediction of Neoadjuvant Chemotherapy Efficacy in Breast Cancer Patients

Abstract: The construction and validation of a radiomics nomogram based on machine learning using magnetic resonance image (MRI) for predicting the efficacy of neoadjuvant chemotherapy (NACT) in patients with breast cancer (BCa). Methods: This retrospective investigation consisted of 158 patients who were diagnosed with BCa and underwent MRI before NACT, of which 33 patients experienced pathological complete response (pCR) by the postoperative pathological examination. The patients with BCa were divided into the trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…DWI and its derived apparent diffusion coefficient (ADC) map also served as a non-contrast MR screening method in lesion detection and distinguishing malignancy from benign tumor (31). Several studies applied radiomics based on breast MRI for the evaluation of malignancy, differentiation of molecular subtype, prediction of receptor expression, and evaluation of response to neoadjuvant therapy in breast cancer (27,(32)(33)(34)(35). Some studies have reported that quantitative parameters of functional MRI, deep learning analysis, and MRI-based radiomics analysis had the potential in predicting molecular subtype and Ki-67 expression in breast cancer (36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…DWI and its derived apparent diffusion coefficient (ADC) map also served as a non-contrast MR screening method in lesion detection and distinguishing malignancy from benign tumor (31). Several studies applied radiomics based on breast MRI for the evaluation of malignancy, differentiation of molecular subtype, prediction of receptor expression, and evaluation of response to neoadjuvant therapy in breast cancer (27,(32)(33)(34)(35). Some studies have reported that quantitative parameters of functional MRI, deep learning analysis, and MRI-based radiomics analysis had the potential in predicting molecular subtype and Ki-67 expression in breast cancer (36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving the diagnostic performance of the model is necessary for the identification of HER-2 2+ status in BC patients. Recent studies showed that a radiomics model constructed by incorporating clinical factors and radiomics score (rad-score) based on radiomic features could improve the predictive ability [23,24]. However, the diagnostic performance of clinical factors and the rad-score based on multiregional DWI and ADC images for evaluating HER-2 2+ status in BC patients has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that various methods could be applied to predict pCR with NAC in breast cancer patients, including analysis of gene signatures, histomorphological factors and imaging features (6)(7)(8). Compared with these methods, serum samples are easy to obtain and reflect the comprehensive state of cancer patients.…”
Section: Introductionmentioning
confidence: 99%